The mission of development: religion and techno-politics in Asia - Scheer, Catherine; Fountain, Philip Michael; Feener, R. Michael (Theology and mission in world christianity, 2018)
Front Matter -- Copyright Page -- Dedication -- Contents -- Preface -- Notes on Contributors -- Development’s Missions /R. Michael Feener and Catherine Scheer -- The Gospel of Intellectuality: Indoctrinating Yenching Educational Missionaries in the Progressive Era /Enyi Hu -- The Laymen’s Foreign Missions Inquiry, the Omi Mission, and Imperial Japan: Missionary Social Science and One Pre-History of Religion and Development /Gregory Vanderbilt -- Missionaries and Mining: Conflicts over Development in Eastern Indonesia /Maribeth Erb and and Fransiska Widyawati -- The New Missionaries of Development: The Indonesian Council of Churches and Village Development Projects, 1971–1982 /Noëmi Rui -- “Development Missionaries” in the Slums of Bangkok: From the Thaification to the De-Thaification of Catholicism /Giuseppe Bolotta -- Developing Faith and Character to Develop the Nation: Perspectives from an Elite Indonesian Catholic School /Erica M. Larson -- Missionaries of a Korean Model of Development: Pentecostalism, Asian Modernity, and the Mission of the Yoido Full Gospel Church in Cambodia /Hui-yeon Kim -- Quietist Techno-Politics: Agricultural Development and Mennonite Mission in Indonesia /Philip Fountain and and Laura S. Meitzner Yoder -- Evangelizing Entrepreneurship: Techno-Politics of Vocational Training in the Global Anti-Human Trafficking Movement /Elena Shih.